ANALISIS SPATIAL PRODUKTIVITAS GARAM DI PULAU JAWA DAN MADURA - MOCH NADJIB YN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
Salt is one of strategic commodities. Beside for public consumption, salt has been created for Iodium fortification to become Iodium consumption salt in order to prevent health disturbance caused by lack of Iodium consumption. Salt also known as one of Sodium and Chloride source, which is needed for metabolism process of human body. From the fact that degradation of productive area is taken place, this study directed into a spatial analysis of public salt productivity using study case methods at three salt concentration area in Java – Madura in order to build basic salting propagation in eastern Indonesia. The study result that is concluded from physical variables (elevation, bed rock type, soil type, climate, salinity), demography variables, and technology variables shown : The salt productivity is increasing much more to the east, equal with the increasing of salting land area. The most significant factor to influence salt quality are production technology and physical factor (bedrock type, soil type, drainage area, salinity). Physical factor is not significantly influence, while all salting land area has the similar physiography that elevated two meters below sea level. The most significant factor is culture and people character. Analysis results for salting land area suitability shown that the existing salting land area at study case area still be able to develop especially at Astanajapura sub-disctrict.